Histological features of carotid plaque in patients with ocular ischemia versus cerebral events. - Howard, D; van Lammeren, G; Redgrave, J; Moll, F; de Vries, J; de Kleijn, D; de Borst, G; Pasterkamp, G; Rothwell, P (2013)
BACKGROUND AND PURPOSE: Patients with carotid artery stenosis and ocular ischemic events have a much lower risk of future ipsilateral ischemic stroke on medical treatment and lower procedural risks for endarterectomy and stenting than patients with cerebral ischemic events, and are closer in risk to patients with asymptomatic stenosis. The reasons for this difference in prognosis are not fully understood, but may reflect differences in carotid plaque pathology. METHODS: In consecutive patients undergoing carotid endarterectomy for recently symptomatic stenosis (Oxford Plaque Study, Athero-Express Study), we compared carotid plaque histology (using validated semiquantitative scales) in those who had cerebral events within the last 6 months (n=1317) versus those with ocular events only (n=323). RESULTS: Compared with plaques from patients with ocular events only, those from patients with cerebral events had significantly more large lipid core (odds ratio [OR], 1.38; 95% confidence interval [CI], 1.05-1.82; P=0.02), inflammation (OR, 1.32; 95% CI, 1.02-1.72; P=0.04) and overall plaque instability (OR, 1.37; 95% CI, 1.05-1.80; P=0.02), and less fibrous content (OR, 0.71; 95% CI, 0.54-0.92; P=0.01), and calcification (OR, 0.70; 95% CI, 0.54-0.91; P=0.008). The overall number of histological features known to be associated with vulnerable plaque was greater in patients with cerebral events than in those with ocular events (P=0.002). CONCLUSIONS: Carotid plaques from patients undergoing endarterectomy for previous ocular ischemic events have fewer vulnerable plaque features than those from patients with recent cerebral ischemic events, possibly explaining some of the differences in risk of stroke between these groups.